The Relationship between Farmer’s Characteristics and Institutions on the Sustainability of Pasundan Cattle Business in Purwakarta Regency (Case in the Tegal Saluyu Group 1 and 2 of Tegalsari Village, Tegalwaru District, Purwakarta Regency) - HASANAH, KINSA RAEHAN; Sulaeman, Mumun Munandar; Wiyatna, Muhamad Fatah (Jurnal Ilmu Ternak Universitas Padjadjaran, 2024)
The research entitled "The Relationship between Farmer’s Characteristics and Institutions on the Sustainability of Pasundan Cattle Business in Purwakarta Regency (Case in Tegal Saluyu Group 1 and 2 of Tegalsari Village, Tegalwaru District, Purwakarta Regency)” was carried out in October 2022, located in Tegalsari Village, Tegalwaru District, Purwakarta Regency. This study aims to determine the farmers’ characteristics, institutions, and their relationship with cattle business sustainability. This research used the case study method. It was conducted on 34 respondents by interview using a questionnaire. The collected data were analyzed using data quality, cross-tabulation, and Rank Spearman correlation analysis. The data processing results indicate the condition of the characteristics of farmers, institutions, and the ideal sustainability of the Pasundan cattle business, as well as a positive and significant relationship between the characteristics of farmers and institutions on the sustainability of the Pasundan cattle business.